Role of The Notary in The Transition of Receivables (CESSIE) on Non-Load Loans in PT Bank Tabungan Negara - Ricky Yulianto Saputro; Tri Lisiani Prihatinah (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The settlement of bad debts through the transfer of receivables (CESSIE) is regulated in Article 613 of the Civil Code. However, in practice, there are problems regarding the mechanism for implementing the transfer of receivables (CESSIE) in the case of the Pekanbaru District Court decision Number 129/Pdt.G/2016/PN.PBR is then on appeal with the decision of the Pekanbaru High Court Number 59/Pdt.G/2017/PT.PBR. This study aims to analyze the mechanism for the transfer of receivables (CESSIE), which is considered valid by applicable legal provisions, and to examine and analyze the role of the Notary in the transfer of receivables (CESSIE). This study uses a normative juridical method, with the research specifications used prescriptively. The writing uses secondary data consisting of primary, secondary, and tertiary legal materials. Methods Data collection using literature study with the method presented in the form of descriptive narrative text. Analysis The data were analyzed in a qualitative normative manner. The research results obtained are 4 (four) stages of the mechanism that are considered valid in settling bad loans through the transfer of receivables (cessie) by PT. Bank Tabungan Negara. First, the credit was declared bad by the Bank, in this case, PT. Bank. Tabungan Negara Second, by implementing the restructuring of credit belonging to debtors who are unable to carry out their performance as they should. Third, PT. Bank Tabungan Negara is required to subpoena 3 (three) times to the Debtor due to default by the Debtor. Fourth, through the transfer of receivables (CESSIE), which is bound by Mortgage Rights and contained in authentic deeds, PT. Bank Tabungan Negara can sell the object of collateral owned without the assistance of the Court. The four stages refer to the provisions of Article 1243 of the Civil Code, Law Number 10 of 1998, concerning Banking and its implementing regulations, namely Bank Indonesia Regulation Number 14/15/PBI/2012 concerning asset quality assessment of commercial banks which is now the Financial Services Authority Regulation Number 40 / POJK.03/2019, and the Mortgage Law. If this fourth stage is not carried out, the mechanism for the transfer of receivables (CESSIE), which the Mortgage Rights do not bind, is still valid but is not related to the transfer of the object of collateral. The Notary's role in transferring receivables (CESSIE) in the case of Decision Number 129/Pdt.G/2016/PN. PBR is not following the provisions of the Law on Notary Positions. What is violated is that the Notary does not provide legal counseling as referred to in Article 15 paragraph (2) letter (e) of the Notary Position Act. The Notary is authorized to provide legal counseling regarding the deed. In the case of a transfer of sale and purchase of receivables (CESSIE), the role of the notary shifts as the Pejabat Pembuat Akta Tanah (PPAT) to transfer the mortgage guarantee from the old creditor (Cedent) to the new creditor (Cessionaris), the Deed of Transfer of Mortgage Rights (APHT) is then registered to the Office of the National Land Agency (BPN), thereby switching Mortgage Rights from the old creditor (Cedent) to the new creditor (Cessionaris). Without the transfer of Mortgage registration, the new creditor (cessionary) only becomes a congruent creditor, not a separatist creditor, and does not have preferential rights in paying off debtors' debts.Keywords: Role of Notary, Bad Credit, Cessie